Development and use of laboratory practical «Based on language Visual basic 2010» in the educational process - Dopira, R.I.; Bazikova, K.M.; Popova, N.V. (KSU Publ., 2016)
The article describes the creation and use in practice of the electronic textbook. It is explored possible means of modern information technologies, the terms of which are required for their successful use is reviewed and analyzed by application soft-ware required to create and further use of electronic textbooks. In addition, we describe all the steps of creating such electronic resources on a specific example of the electronic textbook
«Visual Basic 2010 тілінің негіздері» зертханалық практикумын оқу процесінде пайдалану жəне құру
Разработка и использование лабораторного практикума «Основы языка Visual Basic 2010» в образовательном процессе
Keywords: the educational process; training; bachelor; information technology; elective course; programming; electronic textbooks; laboratory practical; stages of development; the structure of the electronic textbook